Trazabilidad de antibióticos β-lactámicos en el centro de acopio lechero “Toni” Guaranda, mediante técnicas cromatográficas - Tipán Suquillo, Adrián Ricardo (2019)
Residues of β-lactam drugs that can be found in milk intended for human consumption can cause different health problems such as: allergies, anaphylaxis, alterations in the intestinal flora, and create resistance to these antibiotics. Because these substances, no matter how small, are not completely destroyed during industrialization processes. The tests currently used in the dairy industry for the detection of these drugs are by means of test strips, these allow to identify certain groups of drugs, detecting quantities lower than MRLs allowed by the Codex Alimentarius, but these tests do not detect the quantity and the specific drug that is found in milk, through the use of UPLC can identify and quantify the drugs obtaining great benefits for the control of these drugs. During the duration of the investigation, both the test strips (BIOEASY) and UPLC (INSPECTORATE OF ECUADOR) were used, obtaining negative results for all the tests carried out by these two methods in the milk delivered to the TONI milk collection center in GUARANDA.